Pulmonary arterial wedge pressure in healthy subjects: a meta-analysis - Zeder, Katarina; Avian, Alexander; Mak, Susanna; Giannakoulas, George; Kawut, Steven M.; Maron, Bradley A.; Humbert, Marc; Olschewski, Horst; Kovacs, Gabor (The European respiratory journal, 2024)
Based on current international guidelines, pulmonary arterial wedge pressure (PAWP) is critical for differentiating between pre- and post-capillary pulmonary hypertension (PH) and plays an important role in the diagnosis of left heart failure [1, 2]. The current PAWP threshold to define post-capillary PH is >15 mmHg, measured by right heart catheterisation (RHC) in the supine position [1]. Historical data suggest that the upper limit of physiological PAWP may be lower [3–5], although no systematic review and meta-analysis has investigated the normal range of PAWP considering major confounding factors. We aimed to fill this knowledge gap by assessing the normal value of PAWP based on the largest available database of the published literature on pulmonary haemodynamics, also taking into account possible confounding factors, such as age, sex and RHC methodology. Based on invasive haemodynamic measurements in healthy subjects, the upper limit of normal of PAWP in the supine resting position is 13 mmHg, which is dependent on sex, but independent of age and pressure reading https://bit.ly/3zer5cZ